Simplicia Characteristics and Phytochemical Screening of Buni Fruit (Antidesma bunius L. Spreng) - Ningtias, Anggitha; Rani, Zulmai (Indonesian Journal of Science and Pharmacy, 2023)
ABSTRACT Buni fruit is a plant that produces secondary and antibacterial metabolites. The purpose of this study was to identify the characteristics of the berry simplicia and the content of phytochemical compounds in the berry fruit. Starting with the maceration method using 96% ethanol, this study carried out phytochemical screening and characterization tests. The results of the phytochemical screening study showed that compounds such as flavonoids, tannins, saponins, alkaloids, and steroids were found in the ethanol extract of buni fruit. Due to the simplicia characterization, we found a water content of 9.3%, a water-soluble extract of 11.51%, an ethanol-soluble extract of 17.19%, a total ash content of 8.1%, and an acid-insoluble ash content (0.7 %).